A New Paradigm on Language Imperialism: Student-Teachers Voice on English Language Learning - Ratu Sarah Pujasari; Nanak Hikmatullah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Background: The current language policy in Indonesia removed English language programs from the elementary school curricula for fear of constraining children’s first language ability. Many are worried about the impact of the policy. Such policy sparks a debate among scholars and educators. The policy results in worry among those who believe in the importance of learning English, such as parents and English teachers. Methodology: The current study aims to investigate the English student teachers’ belief in the notion of Language Imperialism (LI). Using the descriptive qualitative method, the data were taken from six of the student-teachers interview. Findings: The current research shows that English is not part of imperialism, but rather a form of empowerment and that their future job as an English teacher is not to promote the language but as a way to help their future students in facing a more globalized and competitive world. Conclusion: In the context of English language learning student-teachers see their profession as a platform for empowerment for future generations. They believe that teaching English as a way to promote local cultures and languages to the outside world by using local content in the classroom, contrary to the popular belief that English dominates local languages Originality: The concept of language imperialism recognizes as colonialism. Little attention is given to the perception of student-teachers as a future generation in criticizing the government policy for better feedback. The positive views found, hopefully, will give fruitful decision for the government.